1967
DOI: 10.1037/h0024119
|View full text |Cite
|
Sign up to set email alerts
|

Unlearning, spontaneous recovery, and the partial-reinforcement effect in paired-associate learning.

Abstract: This study tested 2 implications of the extinction model of unlearning. The model predicts that A-B associations, after the learning of A-C, should recover strength spontaneously with time and should resist unlearning better when practiced under partial reinforcement (reduced % ORM). Availability of B and C responses was measured after 1 min., 24 hr., or 48 hr. by MMFR. While control Ss (A-B only) showed slight forgetting over the retention interval, experimental Ss improved their recall of List 1 responses. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

1967
1967
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…polated practice on a seconji list within a traditional Finally, an additional spurce of variation fnay lie retroactive inhibition paradigm (Ceraso & Hender-in the degree of original learning. Richardson and son, 1965;Silverstein, 1967). In this paradigm, Gough chose a criterion'^of tfiree perfect recitations second list recall is superior to first list recall over of a serial list of nonsense syllables.…”
Section: Discussionmentioning
confidence: 99%
“…polated practice on a seconji list within a traditional Finally, an additional spurce of variation fnay lie retroactive inhibition paradigm (Ceraso & Hender-in the degree of original learning. Richardson and son, 1965;Silverstein, 1967). In this paradigm, Gough chose a criterion'^of tfiree perfect recitations second list recall is superior to first list recall over of a serial list of nonsense syllables.…”
Section: Discussionmentioning
confidence: 99%
“…Such 'spontaneous recovery' e ects have been reported on numerous occasions in the pairedassociates paradigm using the MFR (e.g., Briggs, 1954;Underwood, 1948) and MMFR tests (e.g., Forrester, 1970;Silverstein, 1967), although in some studies the e ects were small or absent (e.g., Birnbaum, 1965;Koppenaal, 1963;Slamecka, 1966). An early review of the literature indicated that the presence or absence of a recovery e ect was to some extent dependent on the researchers' method of statistical analysis (A.…”
mentioning
confidence: 96%
“…Recent experiments indicate,however, that rises in first-listrecall are likely to be observed after intervals of the order of half an hour (Forrester, 1970;Kamman & Melton, 1967;Martin & Mackay, 1970;Postman, Stark, & Fraser, 1968;Postman, Stark, & Henschel, 1969;Shulman & Martin, 1970). The conditions under which recovery may be expected after intervals of a day or more (e.g., Abra, 1969;Ceraso & Henderson, 1965, 1966Silverstein, 1967) remain to be fully specified. Taken together, the demonstrations of the phenomenon have been sufficiently frequent, and in the most recent studies consistent and predictable, to support the historical and pragmatic usefulness of the extinction analogy.…”
Section: The Extinction Analogymentioning
confidence: 99%